2015
DOI: 10.1007/s11277-015-2660-3
|View full text |Cite
|
Sign up to set email alerts
|

Design of Cognitive Decision Making Controller for Autonomous Online Adaptive Beam Steering in Free Space Optical Communication System

Abstract: The beam motion is one of the main causes for major power loss which severely degrades the performance of the Free Space Optical Communication (FSOC) system. Designing a suitable controller to correct the beam motion to increase the beam stability at a point becomes significant. This paper presents an investigation on the performance of two types of controller designed for aiming a laser beam to be at a particular spot under dynamic disturbances generated at the transmitter. The experimental nonlinear input-ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The requirement of transmitting power is less in perfect weather, while in bad weather conditions, it is quite large. The findings of many theoretical, methodological, and experimental research on atmospheric turbulence intensity variations, as well as in-depth discussions, can be found in [49][50][51].…”
Section: Fso Communication System: Temporal Challengesmentioning
confidence: 99%
“…The requirement of transmitting power is less in perfect weather, while in bad weather conditions, it is quite large. The findings of many theoretical, methodological, and experimental research on atmospheric turbulence intensity variations, as well as in-depth discussions, can be found in [49][50][51].…”
Section: Fso Communication System: Temporal Challengesmentioning
confidence: 99%
“…2. More details on the digital designs/ interface protocols/simulations techniques and radar signal logging/ analysis/measurement computations in a MATLAB environment can be found in our previous publications [34][35][36][37][38][39]. The received radar signal (DC through 2 kHz in this work) is applied to a PC i.e.…”
Section: Design Of Cw Radar and Its Descriptionsmentioning
confidence: 99%
“…The requirement of transmit power is low in clear weather whereas, in dense weather, it is relatively high to maintain the required data rate and BER. The results and in-depth discussions associated with several theoretical, statistical, and experimental studies carried out on the atmospheric turbulence strength fluctuation can be found in [9,10,27,[41][42][43].…”
Section: Fig 3 Atmospheric Factors Challenging the Installation Of Fmentioning
confidence: 99%